Celebrating our Fifth Year with Cheiron, the Son of Kronos and Philyra - Molinari, Nicholas J. (KOINON: The International Journal of Classical Numismatic Studies, 2022)
Five years. That is how long KOINON has existed, and this is a special time for the journal because we’ve made it past our third barrier. The first was getting an editorial board and I’m still surprised and humbled that so many notable numismatists agreed to help out. The second was formulating the first journal which, I’m happy to report, can be found in hundreds of academic libraries all over the world, along with all subsequent issues. Now we’ve made it to five years and we have passed our third barrier in the sense that we’ve managed to reach a genuine milestone, and this seems like the perfect opportunity to pause and reflect on the significance of our new contribution to the world of numismatics.